2020
DOI: 10.21715/gb2358-2812.2020341110
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos metais pesados nos sedimentos de fundo do alto rio Jequitinhonha em áreas afetadas pela atividade de extração mineral, Diamantina MG

Abstract: A busca de ouro no leito do rio Jequitinhonha foi o principal motivo a atrair os primeiros Bandeirantes a explorar suas águas. Esta longa jornada, iniciada em sua foz, trouxe resultados próximos à sua nascente no distrito de Serro Frio, local atualmente conhecido como Diamantina, no estado de Minas Gerais. Alguns anos após a sua colonização foram também descobertos os diamantes, e esta região ficou marcada pela presença da atividade mineral até os dias atuais. A atividade garimpeira é uma das responsáveis pela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is important to emphasize that the presence of these elements, in addition to their contributions to environmental contamination, can affect human health. Souza and Baggio (2020) found that heavy metals are important environmental contaminants that tend to accumulate in bottom sediments and can be assimilated by organisms because they are in direct contact with them. Arsenic, depending on its form in the environment, has carcinogenic characteristics, and a large part of its intake occurs through contaminated food from the marine environment, where environmental characteristics may favor its absorption (Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to emphasize that the presence of these elements, in addition to their contributions to environmental contamination, can affect human health. Souza and Baggio (2020) found that heavy metals are important environmental contaminants that tend to accumulate in bottom sediments and can be assimilated by organisms because they are in direct contact with them. Arsenic, depending on its form in the environment, has carcinogenic characteristics, and a large part of its intake occurs through contaminated food from the marine environment, where environmental characteristics may favor its absorption (Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%